Aspects of Biblical inspiration - Benoit, Pierre, 1906--; Murphy-O'Connor, J., trans; Ashe, S.K. , trans (Chicago, Ill : Priory Press, 1965)
The author grasps the psychology of the sacred writer, the literary forms he used and the milieu in which he lived and worked. Thus the theology of inspiration is freed from the impasse into which it had been led by a rather one-sided emphasis on the Bible as the Word of God, and therefore entirely different from all other books. This work shows real understanding of the theological principles involved and the importance of the witness of the Bible itself
Conclusion
Translation of Exegese et theologie. Bibliography: p. 5
Keywords: Bible -- inspiration; Revelation